Удосконалення технології роботи вантажної станції в умовах закриття інших малодіяльних станцій - Іськів, Олександр Олексійович; Iskiv, Oleksandr Oleksiiovych (Національний університет "Львівська політехніка", 2025)
Об’єкт досліджень - процес функціонування вантажних станцій України, їх взаємодії з під’їзними коліями. Предмет досліджень - технологічний процес роботи дільниці залізничних перевезень і вантажної станції МД. Мета дослідження - розробка й оцінка ефективності методів удосконалення технічних та технологічних параметрів вантажних станцій, їх взаємодії з під’їзними коліями в сучасних умовах. Методи досліджень – графо-аналітичне моделювання роботи станції із розрахунком техніко-експлуатаційних показників (з використанням програми Excel). У даній роботі розглянуто проблеми функціонування вантажних станцій та способів розвезення місцевих вагонів на дільниці залізничних перевезень, визначені основні недоліки в існуючій технології роботи та пропозиції щодо їх вирішення, проаналізовано досвід науковців у дослідженні й удосконаленні технічних та технологічних параметрів роботи вантажних станцій. Апробацію методів удосконалення технічних та технологічних параметрів виконано на прикладі вантажної станції МД Львівської залізниці, що обслуговує достатньо велике промислове підприємство та декілька інших під’їзних колій, проаналізоване технічне оснащення станції, існуюча технологія роботи, визначені перспективні обсяги місцевої роботи станції МД, виконано технічне нормування тривалості основних технічних і вантажних операцій, перевірена достатність 4 колійного розвитку станції заявленим обсягам вантажної роботи. Після розробки нової технології роботи станції МД запропоновано ряд заходів щодо удосконалення взаємодії станції і під’їзних колій підприємств. Для удосконалення окремих елементів технології роботи станції МД виконано моделювання роботи станції та розраховані основні експлуатаційні показники з використанням спеціального програмного забезпечення. На основі отриманих результатів моделювання визначено більш раціональний варіант організації роботи під’їзної колії цементного комбінату та станції МД загалом за різних вхідних вантажопотоків. Побудовані добові плани-графіки роботи станції МД та розраховані основні показники за варіантами, також розглянуті питання охорони праці та безпеки руху при закріпленні вагонів на станційних коліях. Галузь застосування – інфраструктура АТ УЗ.

In 2022, as a result of a full-scale war, most of Ukraine's oil refineries were destroyed or stopped, which led to a transition to almost 100% import of oil products and the development of small oil depots. However, the strategic task is not only to meet current needs, but also to plan the post-war recovery and development of the oil refining industry. Three scenarios for the recovery of the enterprises' activities were considered and assessed, SWOT analyses were conducted, and it was shown that the potential for using the capacities of each oil refinery is real. Of particular importance is the Drohobych oil refining complex "Halychyna", which already played an important role before the war, and its geographical location becomes critically important for reconstruction and launch. The enterprise has its own access tracks and is serviced by its own shunting locomotive, which is integrated into the technology of operation of the cargo station D. To assess the prospects for increasing cargo operations with oil products at the station D in the post-war period, a forecast of the volume of work was performed, conditionally designated as the 2030 option. The development of a new technology for the station's operation in a graphical form and further calculation of efficiency indicators are possible only after building a similar graphical model for the existing state (option 2025). The SWOT analysis of the first option was used as a basis for improving the technology taking into account the increased volume of work. The need for routing of oil product shipments was separately identified. The second stage of graphical modeling involves determining and analyzing the main indicators of the station's operation, in particular the average downtime of a local car and the indicators of the use of shunting locomotives - both railway and its own access track. The track development of the station and the access track of the Galician oil refining complex does not allow for the effective simultaneous use of two railway locomotives to perform many shunting operations without unproductive expectations, therefore the new technology involves the use of only one railway shunting locomotive. The modeling results are visualized in the form of diagrams, and the average downtime of a local car is calculated in two ways to increase accuracy. The object of research is the functioning of cargo station D in the post-war period and its interaction with the access track of the oil refining complex. The subject of research is the technological process of the D freight station. The purpose of the research is to develop and evaluate the effectiveness of methods for improving the technological and technical parameters of the station and its interaction with the access tracks in the post-war period. Research methods are graphical and analytical modeling of the station's operation with the calculation of key operational indicators using special software. The results obtained can be used at the D station to increase the efficiency of individual elements of the work technology and optimize the delivery of local cars to the directorate's site.
Improvement of the cargo station operation technology under the conditions of closing other low-activity stations
Keywords: 8.275.02.05